Etnomatematika Dalam Rumah Adat Panjalin - Anggita Maharani; Seka Maulidia (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to improve the learning process at school by using culture-based learning that is ethnomatematics at the Panjalin traditional house. The purpose of this study is to explore the culture of the Panjalin community as a medium for learning mathematics. Through culture-based learning, it is expected that students can improve their mathematical learning outcomes. The results showed that there were mathematical concepts and activities at the Panjalin Traditional House. Students learn theories about mathematical concepts, then know the application of these mathematical concepts. The results of the study aimed to review the benefits of ethnomatematics-based mathematics learning that can motivate students and make the results of research on ethnomatematics at Panjalin traditional house as an alternative idea of mathematics learning outside the classroom and used as reference material for the preparation of contextual mathematical problem solving questions.